2022
DOI: 10.1098/rsob.220274
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial biology and dysfunction in secondary mitochondrial disease

Abstract: Mitochondrial diseases are a broad, genetically heterogeneous class of metabolic disorders characterized by deficits in oxidative phosphorylation (OXPHOS). Primary mitochondrial disease (PMD) defines pathologies resulting from mutation of mitochondrial DNA (mtDNA) or nuclear genes affecting either mtDNA expression or the biogenesis and function of the respiratory chain. Secondary mitochondrial disease (SMD) arises due to mutation of nuclear-encoded genes independent of, or indirectly influencing OXPHOS assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 258 publications
0
5
0
Order By: Relevance
“…Mitochondria affects oxidative stress and immune responses by regulating calcium signals and their homeostasis, participating in cell differentiation, signal transduction, and apoptosis. 1 Mitochondrial damage refers to abnormal changes in mitochondrial structure and function, including large-scale loss of mitochondrial DNA, and changes in membrane structure, electron transfer function through the respiratory chain, mitochondrial transmembrane potential difference, etc., 2,3 resulting in mitochondrial oxidative stress, mitochondrial autophagy, mitochondrial DNA mutations, telomere shortening, etc. A large number of studies have confirmed that mitochondrial damage plays an important role in the occurrence and development of respiratory system diseases.…”
Section: The Role Of Mitochondrial Damage In the Occurrence And Devel...mentioning
confidence: 99%
“…Mitochondria affects oxidative stress and immune responses by regulating calcium signals and their homeostasis, participating in cell differentiation, signal transduction, and apoptosis. 1 Mitochondrial damage refers to abnormal changes in mitochondrial structure and function, including large-scale loss of mitochondrial DNA, and changes in membrane structure, electron transfer function through the respiratory chain, mitochondrial transmembrane potential difference, etc., 2,3 resulting in mitochondrial oxidative stress, mitochondrial autophagy, mitochondrial DNA mutations, telomere shortening, etc. A large number of studies have confirmed that mitochondrial damage plays an important role in the occurrence and development of respiratory system diseases.…”
Section: The Role Of Mitochondrial Damage In the Occurrence And Devel...mentioning
confidence: 99%
“…Generally, the term "mitochondrial disease" describes a heterogeneous set of conditions caused by genetic defects in the assembly and/or function of OXPHOS proteins [45]. In fact, mitochondria play a fundamental role in energy production and are essential in numerous cellular processes [35,46]. Consequently, mitochondrial dysfunction often propagates and/or underlies many pathological states, including neurodegenerative diseases [47,48] and the aging process [49,50].…”
Section: Mitochondrial Neurodegenerative Diseasesmentioning
confidence: 99%
“…However, the term "mitochondrial diseases" has recently been broadened to include another set of pathologies, called secondary mitochondrial dysfunctions, caused by mutations in nuclear genes not related to the OXPHOS assembly and activity. They affect diverse mitochondrial functions including, among others, protein biogenesis, mitochondrial morphology and dynamics, lipid biogenesis, and the Krebs cycle (Ceccatelli Berti et al, 2021;Baker et al, 2022). iMD diagnosis remains a challenge given their clinical, biochemical, and molecular heterogeneities.…”
Section: Introductionmentioning
confidence: 99%